Direct observation of orbital ordering in layered manganites - Hatton, P; Wilkins, S; Beale, T; Johal, T; Prabhakaran, D; Boothroyd, A (2005)
Soft X-ray resonant diffraction is a new technique and there exist several examples of large resonant enhancements of charge and magnetic scattering that can be obtained at the Ledges of 3d transition metal oxides. Here we have employed resonant soft X-ray scattering at the manganese L edges which provide a direct measurement of the orbital ordering. We have studied the layered manganite La0 5Sr1 5MnO4 that displays charge. spin, and orbital ordering. Energy scans at constant wavevector show that there are two separate contributions to the observed scattering, direct Goodenough orbital ordering and strong cooperative Jahn-Teller distortions of the Mn3+ ions. Finally we will show how that the charge, spin and orbital degrees of freedom are strongly correlated in these materials.